Zależność między stopą procentową Narodowego Banku Polskiego a zadłużeniem gospodarstw domowych - Utzig, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The monetary policy of central bank influences the cost of money and determines the amount of credit incurred by households. The article presents the impact of National Bank of Poland’s interest rate on household’s liabilities. Theoretical analysis comes to a conclusion that an increase of interest rate will cause the decrease of household’s liabilities. The paper shows research’s results on the basis of data collected in the period of 2003–2011. Relationship between monetary policy and household’s liabilities was presented with reference to long-term and short-term debt.